Emotions and Beliefs when Learning Math - Estrada Esquivel, Ana Luisa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The research problem was the high levels of failure in mathematics in a Mexican University. The influence of beliefs and emotions on mathematical learning was studied. Data was collected through a validated test about 4 dimensions and 12 indicators, in a sample of 471 students with insufficient and sufficient qualification. A concurrent triangulation design was used for data analysis. The existence of beliefs and emotions was verified, its was classified and described. The importance of emotional management in the teaching and learning processes of mathematics was concluded.